Exploring the Migration to a Digitalised Curriculum at UKZN - Simon Bheki. Khoza (MDPI AG, 2021)
The COVID-19 revolution has demanded that higher education institutions (HEIs) in South Africa, as in most other countries globally, migrate to a digitalised curriculum (DC). The DC is a plan for or of digital technology-driven education. The COVID-19 revolution compelled the University of KwaZulu-Natal (UKZN) to migrate to a DC in order to complete the 2020 academic year or calendar. Pragmatism, critical discourse analysis (CDA), and community of inquiry (CoI) with natural identity (NI) framed the document analysis used to generate data for this study. Purposive convenience sampling was used to select the published documents that carry information on the migration to a DC at UKZN. It was for this reason that this study explored and understood the migration to a DC at UKZN through the use of digital resources. Findings suggested that, while the UKZN had the professional identity of migration through engaging Moodle, it began the migration through the use of WhatsApp, Facebook, Skype, and Zoom video conferencing technology (ZVCT), promoting societal identity. The migration seemed to miss the personal or pragmatic identity as an important ingredient of a DC, which addresses individual personal needs. Consequently, this study recommends a DC that balances performance-based, competence-based, and pragmatic/personal identities in order to address professional, societal, and personal needs, respectively, for natural identity realisation.